Power calculation of novel single-piece aspheric diffractive trifocal intraocular lens - K.B. Pershin; N.F. Pashinova; M.M. Konovalova; A.Yu. Tsygankov; M.E. Konovalov (РМЖ "Клиническая офтальмология")
K.B. Pershin1, N.F. Pashinova1, M.M. Konovalova2, A.Yu.Tsygankov1, M.E. Konovalov2 1LLC “SovMedTech”, Moscow, Russian Federation 2LLC “Ophthalmocenter”, Moscow, Russian Federation Aim: to analyze the efficacy of six IOL power calculation formulas for novel single-piece aspheric trifocal diffractive intraocular lens (IOL). Patients and Methods: retrospective study included 65 patients (100 eyes) with presbyopia who underwent cataract surgery or refractive lens exchange with implantation of novel multifocal IOL AcrySof PanOptix® trifocal. IOL power was calculated using six formulas, i.e., SRK/T (35%), Holladay 2 (18%), Hoffer Q (9%), Haigis (22%), and Barrett Universal II (16%). Efficacy of Barrett Universal II, Haigis, Hoffer Q, Holladay 2, Olsen, and SRK/T formulas using relevant constants was analyzed retrospectively. IOL power ranged from 13 D to 30 D. Results: optimized IOL constants were as follows: LF=2.14 for Barrett Universal II; a0=1.45, a1=0.4; a2=0.1 for Haigis; pACD = 5.71 for Hoffer Q; ACD=5.63 for Holladay 2; ACD=4.79 for Olsen; and А=119.2 for SRK/T. The lowest mean absolute error (MAE) was demonstrated for Barrett Universal II, the greatest MAEs for Holladay 2 and Hoffer Q. 67% of eyes in Barrett Universal II group, 62% of eyes in Olsen group, and more than 50% of eyes in Haigis group were within the ± 0.25 D range from the predicted refraction. Less than 50% of eyes in Hoffer Q, Holladay 2, and SRK/T groups were within the ±0.25 D range from the predicted refraction. More than 90% of eyes were within the ±1.00 D range and more than 95% of eyes were within the ±2.00 D range from the predicted refraction. Conclusions: the lowest mean absolute error and the greatest rate of target refraction achievement were in Barrett Universal II and Olsen groups. These formulas can be recommended for everyday ophthalmic practice. Keywords: cataract, phacoemulsification, trifocal IOL, IOL power calculation, constant optimization, Barrett Universal II, Olsen. For citation: Pershin K.B., Pashinova N.F., Konovalova M.M. et al. Power calculation of novel single-piece aspheric diffractive trifocal intraocular lens. Russian Journal of Clinical Ophthalmology. 2019;19(3):171–174. About the authors: 1Kirill B. Pershin — MD, PhD, Professor, Medical Director, ORCID iD 0000-0003-3445-8899; 1Nadezhda F. Pashinova — MD, PhD, Head Doctor, ORCID iD 0000-0001-5973-0102; 2Mariya M. Konovalova — MD, ophthalmologist, ORCID iD 0000-0003-3597-2101; 1Alexandr Yu. Tsygankov — MD, PhD, Scientific Referent of Medical Director, ORCID iD 0000-0001-9475-3545; 2Mikhail E. Konovalov — MD, PhD, Head Doctor, ORCID iD 0000-0002-3954-6233. 1LLC “SovMedTech”. 3/1, Marksistskaya str., Moscow, 109147, Russian Federation. 2LLC “Ophthalmocenter”. 56/6, 3rd Tverskaya-Yamskaya str., Moscow, 125047, Russian Federation. Contact information: Alexandr Yu. Tsygankov, e-mail: alextsygankov1986@yandex.ru. Financial Disclosure: no author has a financial or property interest in any material or method mentioned. There is no conflict of interests. Received 24.01.2019.